Análise da aplicação de modelos de otimização linear na solução de problemas de dimensionamento de lotes e sequenciamento da produção de bebidas. - Noble Ramos, Victor Mario (2017)
This dissertation adresses the general integrated lot sizing and scheduling problem for non-alcoholic beverage production with synchronization between stages and operating time windows for scheduling preventive maintenances. The problem is characterized by having two interdependent synchronized stages. In the first stage, machines (tanks) can supply several filling lines at the same time in the second stage, where the final items are packed. Production sequence-dependent times and costs exist. The review of the related literature indicates that existing models refer, generally, to particular cases of the general problem adressed here, the most common cases are the dedication of tanks to the lines, and disregarding the perishability of syrups and the possibility of scheduling preventive maintenances. A mathematical model for the general problem, called SMMRPM, has been proposed and applied in several instances to show the adherence and flexibility of the model to represent practical cases that can be found in reality. For the case of the dedication of tanks to lines, the model was compared with the dedicated model F1 (FERREIRA et al, 2012). The results indicate that the SMMRPM model is flexible and adherent to represent practical scenarios in which other models are not applicable, for example the possibility of scheduling preventive maintenance and consideration of perishability are differential of the proposal. In the plans obtained, it was shown that it is important to include these considerations that significantly affect the productive plans. In the case of dedication, compared to the dedicated model, the formulation SMMRPM achieves production plans, on average, 52.63 % less costly than F1.